2018
DOI: 10.2334/josnusd.17-0337
|View full text |Cite
|
Sign up to set email alerts
|

Salivary nitrate-nitrite conversion capacity after nitrate ingestion and incidence of <i>Veillonella</i> spp. in elderly individuals

Abstract: Dietary nitrate has several beneficial effects, including blood pressure reduction and improved oxygen consumption efficiency, but in order to do so it must first be reduced to nitrite by oral bacteria. Veillonella spp., a strictly anaerobic group, are the most prevalent nitrate-reducing bacteria in the oral cavity. In response to some early studies that have hinted at inter- and intra-individual variation in salivary nitrate-nitrite conversion capacity, the purpose of the present study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Veillonella , Actinomyces , Rothia , and Staphylococcus have been identified as the predominant NO 2 − -producing bacteria in the oral cavity 12 . In addition, these genera were also detected in the saliva of adults and newborns 13 , and the frequency of Veillonella was associated with NO 2 − -producing activity in saliva 14 . However, no previous study has examined the NO 2 − -producing activity of the oral biofilm per unit wet weight, or interindividual differences in the composition of NO 2 − -producing bacterial populations at the bacterial species level.…”
Section: Introductionmentioning
confidence: 97%
“…Veillonella , Actinomyces , Rothia , and Staphylococcus have been identified as the predominant NO 2 − -producing bacteria in the oral cavity 12 . In addition, these genera were also detected in the saliva of adults and newborns 13 , and the frequency of Veillonella was associated with NO 2 − -producing activity in saliva 14 . However, no previous study has examined the NO 2 − -producing activity of the oral biofilm per unit wet weight, or interindividual differences in the composition of NO 2 − -producing bacterial populations at the bacterial species level.…”
Section: Introductionmentioning
confidence: 97%
“…V. atypica is commonly isolated from the oral cavity and has been studied extensively at this anatomical site [18][19][20][21][22] . In the oral microbiome, V. atypica is considered a 'bridging species' that enables the colonization of middle and late colonizers to the oral plaque biofilm, with the aid of initial colonizing species, therefore V. atypica promotes oral biofilm development [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Boss et al [4] observed large variation between subjects in salivary nitrate/nitrite concentrations after nitrate loading, and concluded that it was possible to discriminate between subjects with consistently high or low nitrite conversion rates. We recently reported that the correlation coefficients between two measurements of Δ nitrate and Δ nitrite after nitrate ingestion in the same individual, separated by a 7-day interval, were 0.637 and 0.583, respectively (n = 24, p < 0.01) [6]. The inter-individual Fig.…”
Section: Discussionmentioning
confidence: 85%
“…To confirm the DNA band of each primer, PCR agarose gel procedures were performed for all participants. The details of these procedures have been previously described [6].…”
Section: Bacterial Strain Culture Conditions and Specific Primersmentioning
confidence: 99%